Quality Management in Early Childhood Education at State Kindergarten Pembina Tanjung Redeb - Nur Khayati; Azainil Azainil; Haeruddin Haeruddin (Dinasti International Journal of Education Management And Social Science, 2025)
Early Childhood Education (ECE) plays a crucial role in shaping children's developmental foundations, making quality management a vital aspect of ensuring optimal educational services. The main focus includes planning, organizing, implementation, supervision, as well as challenges and strategic solutions in applying quality management in the school. This research employs a qualitative approach with a case study method. Data were collected through interviews, observations, and documentation, then analyzed using data reduction, data presentation, and verification techniques. The findings indicate that quality management at TK Negeri Pembina Tanjung Redeb has been implemented through various planning strategies, including annual program development and curriculum enhancement. In terms of organization, the school principal plays a central role in forming a solid team to improve the effectiveness of educational management. The implementation of quality management is reflected in strengthening teacher competencies, optimizing facilities and infrastructure, and enhancing play-based learning methods. Supervision is conducted through routine evaluations of teacher performance and student development. However, this study also identifies several challenges, such as limited resources, low teacher welfare, and a lack of parental involvement. To overcome these challenges, recommended strategies include regular teacher training, increased support from stakeholders, and optimal utilization of available resources. The findings of this study are expected to contribute to the development of quality management policies in PAUD, particularly in the context of continuous improvement to enhance early childhood education services.